Prognostic Factors of Recurrence and Survival in Vulvar Melanoma: Subgroup Analysis of the VULvar CANcer Study. Issue 7 (September 2016) - Iacoponi, Sara; Rubio, Patricia; Garcia, Enrique; Oehler, Martin K.; Diez, Javier; Diaz-De la Noval, Begoña; Mora, Pablo; Gardella, Barbara; Gomez, Ivan; Kotsopoulos, Ioannis C.; Zalewski, Kamil; Zapardiel, Ignacio
Abstract : Objective: The aim of this study was to analyze the prognostic factors related to the recurrence rate and overall survival of vulval melanoma patients by means of a subgroup analysis of the VULvar CANcer study. Methods: The international multicenter VULvar CANcer study involved 100 international centers, which contributed 2453 vulvar cancer cases. Of the 1727 patients finally included in the study, 42 were suffering from vulvar melanoma (2.4%). Results: The mean follow-up for vulval melanoma patients was 44.1±35.7 months. Recurrence rate was 50%, and the mean recurrence-free survival was 43.5±6.6 months. For local recurrences, the mean recurrence-free interval was 63.3±8.6 months; for metastasis, 33.5±3.5 months. The 5-year recurrence-free survival rate was 28.6%. The mean overall survival for vulvar melanomas was 45.9±4 months and the 5-year overall survival rate was 78.6%. The only factor with prognostic significance regarding local recurrence of vulvar melanoma was tumor size ( P = 0.003). American Joint Committee on Cancer staging was the only prognostic factor associated with metastatic disease at recurrence ( P < 0.001). Finally, age of patient was significantly associated with overall survival ( P < 0.001). Conclusions: Tumor size and American Joint Committee on Cancer stage were independent prognostic factors associated with local and distant recurrence, respectively. Patients' age was the only independent prognostic factor associated with overall survival.